The Role of Customer Engagement and Ads Creativity in Mediating and Moderating the Effect of Social Media Marketing on Purchase Decision: A Study on Kedai Kopi Kulo Consumers - Swissa, Indira Ratu; Supriadi, Asep; Setya, Yanto Azie (PT Larva Wijaya Penerbit, 2025)
This study examines the effect of social media marketing on purchase decisions with customer engagement as a mediating variable and ads creativity as a moderating variable. A quantitative approach was applied using a survey method. Data were collected from 152 respondents who are customers of Kedai Kopi Kulo and active Instagram users. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that social media marketing does not have a significant direct effect on purchase decisions. However, it has a significant positive effect on customer engagement, which in turn significantly influences purchase decisions. Furthermore, customer engagement successfully mediates the relationship between social media marketing and purchase decisions. Ads creativity was found to negatively moderate the relationship between social media marketing and purchase decisions. These findings suggest that while social media marketing alone may not directly drive purchase decisions, its influence becomes effective when it fosters strong customer engagement. The study also highlights the importance of creative advertising in shaping consumer responses, though excessive creativity might weaken the effectiveness of social media marketing in some contexts.